POTENSI PERKEMBANGAN AGROWISATA DI KABUPATEN KERINCI - Lily Zuriati; Sri Mariya (JURNAL BUANA, 2020)
This study aims to obtain information about 1) the potential of agrotourism in Kerinci Regency, 2) The feasibility of agrotourism in Kerinci Regency. This type of research is descriptive qualitative and quantitative research (mixed methods). Data collection techniques were obtained from interviews with landowners, tourists and related agencies. How to determine the sample by means of total sampling that is the number of samples equal to the total population. Data analysis techniques consisted of descriptive analysis and analysis of the suitability and feasibility of agrotourism. The results showed that (1) Kerinci Regency has the potential of orange citrus agro-tourism in Lolo Kecil Village, salak pondoh in Kebun Baru Village and durian in Pulau Tengah Village. (2) the results of the criteria of agro-tourism feasibility (KKA) for orange citrus plantations are very potential, KKA for salak pondoh plantations that is potential, KKA for durian plantations that is potential.